Risky sexual behaviour and contraceptive use in contexts of displacement: insights from a cross-sectional survey of female adolescent refugees in Ghana - John Kuumuori Ganle; Doris Amoako; Leonard Baatiema; Muslim Ibrahim (International Journal for Equity in Health, 2019)
Abstract Background Difficulty in accessing sexual and reproductive healthcare is one of the challenges young refugee women face worldwide, in addition to sexual exploitation, violence and abuse. Although Ghana hosts several refugees, little is known about their sexual behaviour and contraceptive use. This study assesses sexual behaviour and contraceptive use among female adolescent refugees in Ghana. Methods A cross-sectional survey was conducted between June and August 2016. Respondents comprised 242 female adolescent refugees aged 14–19 years. Structured validated questionnaires were used to collect data. Descriptive statistical methods and multivariate logistic regression statistical analyses methods were used to analyze data. Findings Over 78% of respondents have had penetrative sex; 43% have had coerced sex; 71% have had transactional sex; 36% have had sex while drunk, 57% have had 4–6 sexual partners in the last 12 months before the study, and 38% have had both coerced and transactional sex. Factors that predicted ever having transactional sex included being aged 14–16 compared to those aged 17–19 (AOR =4·80; 95% CI = 2·55–9·04); being from Liberia compared to being from Ghana (AOR = 3·05; 95% CI = 1.69–13·49); having a mother who had no formal education compared to having a mother with tertiary education (AOR = 5.75; 95CI = 1.94–14.99); and living alone (self) compared to living with parents (AOR = 3.77; 95CI = 1.38–10.33). However, having 1–3 sexual partners in the last 12 months as against having 4–6 partners significantly reduced the odds of ever having transactional sex (AOR = 0·02; 95% CI = 0·01–0·08). Awareness about contraceptives was 65%, while ever use of contraceptives was 12%. However, contraceptive use at last sexual intercourse was 8.2%, and current use was 7.3%. Contraceptive use was relatively higher among those who have never had sex while drunk, as well as among those who have never had transactional sex and coerced sex. Contraceptive use was similarly higher among those who had 1–3 sexual partners in the last 12 months compared to those who had 4–6 during the same time period. Conclusion In this time of global migration crises, addressing disparities in knowledge and access to contraception as well as high risk sexual behaviours in refugee situations is important for reducing inequalities in reproductive health outcomes and ensuring both universal health coverage and global health justice. Sex and contraception education and counselling, self-efficacy training, and skills acquisition are needed to help young refugee women negotiate and practice safe sex and resist sexual pressures.